2x(x+1)-2=2(x-2)(x+3)

Simple and best practice solution for 2x(x+1)-2=2(x-2)(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x+1)-2=2(x-2)(x+3) equation:



2x(x+1)-2=2(x-2)(x+3)
We move all terms to the left:
2x(x+1)-2-(2(x-2)(x+3))=0
We multiply parentheses
2x^2+2x-(2(x-2)(x+3))-2=0
We multiply parentheses ..
2x^2-(2(+x^2+3x-2x-6))+2x-2=0
We calculate terms in parentheses: -(2(+x^2+3x-2x-6)), so:
2(+x^2+3x-2x-6)
We multiply parentheses
2x^2+6x-4x-12
We add all the numbers together, and all the variables
2x^2+2x-12
Back to the equation:
-(2x^2+2x-12)
We add all the numbers together, and all the variables
2x^2+2x-(2x^2+2x-12)-2=0
We get rid of parentheses
2x^2-2x^2+2x-2x+12-2=0
We add all the numbers together, and all the variables
10!=0
There is no solution for this equation

See similar equations:

| -42-11x+15x=94 | | 2(p-10)=14 | | V=3.14(8.5/2)^2x12 | | 3x-x^2=-54 | | -45+12x-6x=93 | | -35=-9x+2x | | 3j^2+16j+13=0 | | 5.5x32=57 | | 6y+8=5y+8 | | 12•n=3 | | 36=-3(n+10) | | 4y−y+11=38 | | 1/2x+3=5/8x-1 | | -16=4(d+6) | | |p+3|=10 | | 3(1-3v)=-4(2v-3) | | 6y-9=9y-4y | | |2t+3|+2=9 | | 2(x+)=3x-1 | | 32=5n+4 | | -3=3x-6x | | 3(x+5)-5x=2(-4x+8) | | -38-4r=-7(8r-2) | | -3-6p=9 | | 6=-2(7-c | | 12x-18+54=180 | | 32w^2-64=0 | | -6x+9x=-3 | | 5n+4=32 | | 5*11*n=55 | | −5p^​3−5p^​2+60p=0 | | 3/7*t=6 |

Equations solver categories